1999
DOI: 10.1029/1999ja900311
|View full text |Cite
|
Sign up to set email alerts
|

Solar causes of the long‐term increase in geomagnetic activity

Abstract: Abstract. We analyze the causes of the century-long increase in geomagnetic activity, quantified by annual means of the aa index, using observations of interplanetary space, galactic cosmic rays, the ionosphere, and the auroral electrojet, made during the last three solar cycles. The effects of changes in ionospheric conductivity, the Earth's dipole tilt, and magnetic moment are shown to be small; only changes in near-Earth interplanetary space make a significant contribution to the long-term increase in activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
137
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(154 citation statements)
references
References 59 publications
11
137
1
2
Order By: Relevance
“…Parker spiral theory predicts the heliospheric field components in heliocentric polar (r s , φ, ψ) coordinates will be: Stamper et al (1999) and Gazis (1996) have shown that this theory correctly predicts B ψ = 0 and the garden hose angle γ in annual means. In addition, the value of γ is almost constant in annual mean data from near Earth.…”
Section: Estimating the Coronal Source Fluxmentioning
confidence: 99%
“…Parker spiral theory predicts the heliospheric field components in heliocentric polar (r s , φ, ψ) coordinates will be: Stamper et al (1999) and Gazis (1996) have shown that this theory correctly predicts B ψ = 0 and the garden hose angle γ in annual means. In addition, the value of γ is almost constant in annual mean data from near Earth.…”
Section: Estimating the Coronal Source Fluxmentioning
confidence: 99%
“…Still, it illustrates the possibility that magnetic perturbations at high latitudes could also be affected by main magnetic field changes, which should be investigated further with a more appropriate model. If long-term changes in the geomagnetic field affect the magnetic perturbations associated with geomagnetic storms, this could have important implications for the interpretation of reported trends in geomagnetic activity (e.g., Stamper et al 1999;Clilverd et al 2002).…”
Section: Solar Quiet (Sq) Daily Amplitudementioning
confidence: 99%
“…One parameterization of the solar wind energy input into the magnetosphere is the e parameter (Perrealt & Akasofu 1978) given by e ¼ l 2 0 V sw B 2 sin 4 ðh=2Þ, where l 2 0 is the area of the magnetopause through which the energy enters, V SW is the solar wind speed, B is the magnetic field intensity, and h is the ''clock angle'' of the IMF relative to the Sun-Earth line; e has the form of the Poynting flux in the upstream solar wind. Thus, geomagnetic activity reflects conditions in the solar wind that encounters the Earth which in turn are influenced by both long-term changes and transient activity at the Sun (e.g., Russell 1975;Feynman & Crooker 1978;Stamper et al 1999;Richardson et al 2000Richardson et al , 2002aRichardson et al , 2002bSvalgaard & Cliver 2010;Richardson & Cane 2012a;and references therein).…”
Section: Introductionmentioning
confidence: 99%